The growth restriction effect of TiCN nanoparticles on Al-Cu-Zr alloys via ultrasonic treatment - Yiwang Jia (Elsevier, 2021)
Ex situ and in situ synchrotron X-radiography study on Al-Cu-Zr alloys with addition of Al-5Ti-1B and TiCN nanoparticles (TiCNnp) were carried out at different cooling rates. Al-Zr alloy can be effectively refined by TiCNnp via Ultrasonic treatment as compared with Al-5Ti-1B which has Zr poisoning effect. The influence of cooling rate on the nucleation and growth of grains have been studied quantitatively. The results show that the grain size was decreased and the growth rate was increased with the increasing of cooling rate. At the same cooling rate, the grain size with addition of 0.5% TiCNnp was smaller than that with the same addition of Al-5Ti-1B. The blocking factor f of TiCNnp decreases with increasing cooling rate. Based on the free growth model, a new numerical model considering the growth restriction effect of nanoparticles was established. The growth of grain was inhibited by the combining effect of solute and nanoparticles. The growth rate of grain is reduced due to part of the solid/liquid interface coated by nanoparticles. The blocking factor f is linearly decreased with the coverage ratio ω which is proportional to the critical grain radius. The grain size decreases with increasing cooling rate and decreasing f . This study is especially beneficial for Al alloys that have poisoning phenomenon inoculated by traditional refiner.